2018
DOI: 10.1101/428854
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CrRLK1L receptor-like kinases HERCULES RECEPTOR KINASE 1 and ANJEA are female determinants of pollen tube reception

Abstract: Communication between the gametophytes is vital for angiosperm fertilisation. Multiple CrRLK1L‐type receptor kinases prevent premature pollen tube burst, while another CrRLK1L protein, FERONIA (FER), is required for pollen tube reception in the female gametophyte. We report here the identification of two additional CrRLK1L homologues, HERCULES RECEPTOR KINASE 1 (HERK1) and ANJEA (ANJ), which act redundantly to promote pollen tube growth arrest at the synergid cells. HERK1 and ANJ localise to the filiform appar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(40 citation statements)
references
References 61 publications
2
38
0
Order By: Relevance
“…We therefore next tested membrane targeting of ANX1-GFP and BUPS2-GFP and observed that these receptors have normal membrane localization even without LLG2/3 (Figure S5B). A similar localization at the synergid plasma membrane was recently reported for the CrRLK1Ls HERK1 and ANJEA [33]. Next, we investigated the interactions among LLG2/3, the BUPS-ANX receptor complex, and the peptide ligands RALF4/19.…”
Section: Llg2/3 Are Involved In Ralf4/19-mediated Signaling As Co-receptorssupporting
confidence: 70%
“…We therefore next tested membrane targeting of ANX1-GFP and BUPS2-GFP and observed that these receptors have normal membrane localization even without LLG2/3 (Figure S5B). A similar localization at the synergid plasma membrane was recently reported for the CrRLK1Ls HERK1 and ANJEA [33]. Next, we investigated the interactions among LLG2/3, the BUPS-ANX receptor complex, and the peptide ligands RALF4/19.…”
Section: Llg2/3 Are Involved In Ralf4/19-mediated Signaling As Co-receptorssupporting
confidence: 70%
“…As pollen tubes approach ovules, ovule-expressed AtRALF34 peptide competes with pollen-expressed AtRALF4 and 19 for binding to ANX1/2 or BUPS1/2, allowing sperm cell discharge (Ge et al, 2017). Recently, two CrRLK1L receptor-like kinases, HERCULES1 (HERK1) and ANJEA (ANJ), were identified as female determinants of pollen tube reception (Galindo-Trigo et al, 2019). Both HERK1 and ANJ interact with FER and, although not yet proved, an analogous mechanism was proposed where pollen-derived RALFs would act upon receptor heterocomplexes made of FER, HERK1 and ANJ assembled on female tissues to control pollen tube reception (Galindo-Trigo et al, 2019).…”
Section: Regulation Of Cell Physiology Growth and Developmental Procmentioning
confidence: 99%
“…Recently, two CrRLK1L receptor-like kinases, HERCULES1 (HERK1) and ANJEA (ANJ), were identified as female determinants of pollen tube reception (Galindo-Trigo et al, 2019). Both HERK1 and ANJ interact with FER and, although not yet proved, an analogous mechanism was proposed where pollen-derived RALFs would act upon receptor heterocomplexes made of FER, HERK1 and ANJ assembled on female tissues to control pollen tube reception (Galindo-Trigo et al, 2019). Fertilization is the result of an interplay between signal molecules, their receptors, second messengers and cell wall components.…”
Section: Regulation Of Cell Physiology Growth and Developmental Procmentioning
confidence: 99%
“…Other malectin-like RLKs involved in plant reproduction are HERCULES RECEPTOR KINASE 1 (HERK1) and ANJEA (ANJ). During fertilization, HERK1 and ANJ interact with FER to regulate pollen tube reception (Galindo-Trigo et al, 2020). Additionally, malectinlike RLKs BUDDHA'S PAPER SEAL 1/2 (BUPS1/2) and ANX1/2 were reported to play a role in plant reproduction by controlling the pollen tube's cell wall integrity during fertilization (Boisson-Dernier et al, 2009;Miyazaki et al, 2009;Ge et al, 2017).…”
Section: Rlks and Rlps With Distinct Extracellular Domains In Plant Gmentioning
confidence: 99%
“…Meanwhile, the MAPK cascade downstream of chitin and CERK1 pathway consists of MEKK‐MKK4/MKK5‐MPK3/MPK6 (Miya et al, 2007; Meng and Zhang, 2013). Likewise, plant response to DAMPs leads to activation of WAK receptors that will transduce the signal through the MPK3/MPK6 cascade (Denoux et al, 2008; Galletti et al, 2011; Meng and Zhang, 2013). MAPK activation often leads to the expression of immune‐related genes, ROS production, stomatal closure, ethylene production, and hypersensitive response (Meng and Zhang, 2013).…”
Section: Intracellular Signaling Upon Activation Of Rlk Rlp and Rlck Complexesmentioning
confidence: 99%